On-line measurement of soil properties without direct spectral response in near infrared spectral range - Marín-González, Omar; Kuang, Boyan Y.; Quraishi, Mohammed Z.; Munóz-García, Miguel Ángel; Mouazen, Abdul Mounem (Elsevier, 2013)
So far, the majority of reports on on-line measurement considered soil properties with direct spectral responses in near infrared spectroscopy (NIRS). This work reports on the results of on-line measurement of soil properties with indirect spectral responses, e.g. pH, cation exchange capacity (CEC), exchangeable calcium (Ca-ex) and exchangeable magnesium (Mg-ex) in one field in Bedfordshire in the UK. The on-line sensor consisted of a subsoiler coupled with an AgroSpec mobile, fibre type, visible and near infrared (vis-NIR) spectrophotometer (tec5 Technology for Spectroscopy, Germany), with a measurement range 305-2200 nm to acquire soil spectra in diffuse reflectance mode. General calibration models for the studied soil properties were developed with a partial least squares regression (PLSR) with one-leave-out cross validation, using spectra measured under non-mobile laboratory conditions of 160 soil samples collected from different fields in four farms in Europe, namely, Czech Republic, Denmark, Netherland and UK. A group of 25 samples independent from the calibration set was used as independent validation set. Higher accuracy was obtained for laboratory scanning as compared to on-line scanning of the 25 independent samples. The prediction accuracy for the laboratory and on-line measurements was classified as excellent/very good for pH (RPD = 2.69 and 2.14 and r(2) = 0.86 and 0.78, respectively), and moderately good for CEC (RPD = 1.77 and 1.61 and r(2) = 0.68 and 0.62, respectively) and Mg-ex (RPD = 1.72 and 1.49 and r(2) = 0.66 and 0.67, respectively). For Ca-ex, very good accuracy was calculated for laboratory method (RPD = 2.19 and r(2) = 0.86), as compared to the poor accuracy reported for the on-line method (RPD = 1.30 and r(2) = 0.61). The ability of collecting large number of data points per field area (about 12,800 point per 21 ha) and the simultaneous analysis of several soil properties without direct spectral response in the NIR range at relatively high operational speed and appreciable accuracy, encourage the recommendation of the on-line measurement system for site specific fertilisation